IMPLEMENTASI DIGITALISASI PEMBELAJARAN DI SMK MIFTAHUL ULUM UNGARAN TIMUR, KABUPATEN SEMARANG - Ninik Kristanti; Noor Miyono (STKIP Subang, 2024)
The development of the digital world is happening so dynamically, sooner or later it will not only influence but change the direction of education quality policy. For this reason, this journal aims to examine the implementation of digitalization of learning at Miftahul Ulum Vocational School Ungaran in facing the era of revolution 4.0 towards 5.0 and what obstacles are faced in implementing digitalization of learning. This research uses descriptive qualitative research. Data collection techniques use observation, interviews and documentation studies. Test the validity of this research using the triangulation test. Data analysis techniques use collecting data, condensing data, presenting data/verification and drawing conclusions.